Biodisponibilidade e toxicidade de contaminantes em sedimentos na porção nordeste da Baía de Todos os Santos - Garcia, Karina Santos (2009)
The purpose of this study the quality of the sediment surface of the northeast portion of the Todos os Santos Bay through the application of the sediment quality triad. For samples that were collected from surface sediment samples in eight seasons (Coqueiro Grande (1-CG), Mataripe (2-MA, 3-MA, 4-MA, 5-MA), Caípe (6-CA), Suape (7-SU) e Coqueiro Grande (8- CG)) in the northern portion of the Todos os Santos Bay-BA, (TSB). It was determined the spatial distribution of acid volaties sulfides (AVS) and simultaneously extracted metal (SEM)- (Cd, Cu, Pb, Ni and Zn), nutrients (C.O, Ntotal), TPH and PAH by GC/MS. They also evaluated the size, pH and Eh of the sediment. The AVS was extracted from the anaerobic sediment with hydrochloric acid 1 mol L-1, the cold, and the divalent metals released during this treatment are referred to as simultaneously extracted metals (SEM). The method of hydrocarbons followed USEPA. The tests were performed Ecotoxicological sediments with benthic copepods Tisbe biminiensis. Samples of macrozoobentos were collected, counted and identified to the level taxonomic family. Tests showed statistical difference between the stations. The results obtained by reason AVS/SEM, were correlated with the size fractions, total organic carbon (0.14 11.6%), total nitrogen (0.02 0.25%), metals [Cd (<0.10 0.26 μg g-1), Cu (0.04 35.42 μg g-1), Pb (0.02 9.85 μg g-1), Ni (<0.07 4.76 μg g-1), Zn (16.74 38.39 μg g-1)]. Compared to the results with international reference values (National Oceanic and Atmosferic Administration - NOAA and Summary of Existing Canadian Environmental Quality Guidelines) it was found to be below the set, when even compared with those found in other regions of Brazil. There was still, values <1 for the ratio [SEM] / [AVS], not suggesting the bioavailability of these metals, except in stations 1-CG, 2-MA, 5- MA- and 7SU (1st collection) and 1-CG (2nd collection). The results ecotoxicological test with the Tisbe biminiensis had sub-lethal effects in the CG-stations, 2-MA, 5-MA and 7 -SU (1st collection). The screening resulted in a total of 1333 bodies belonging to only 6 phylo. The groups of highest species richness were Mollusca (12), the Annelida - Polychaeta (8), beyond the Arthropoda - Crustacea (6), which accounted for 97.8% of taxonomic unit sampled. It was found that the stations located in spite of not showing mesolitoral values of density, richness and diversity much higher than the stations located in infralitoral show a distinct pattern of distribution with dominance of polychaetes specifies indicators of organic contamination as Capitellidae. The bivalve (Anomalocardia brasiliana, Tellina sp., Tagelus plebeius) and polychaetes (Capitella sp., Laeonereis acuta, Glycinde multidens) were the most representative species. The richness of species, relatively low, observed in the study area, may be related to the occurrence of the high percentage of mud, which has been described by previous work that the associations are faunistic poorest. The integration of the Triad using the table for a decision to classify the area into 4 categories: 1st collection: high quality (8-GC), intermediate/high quality (3-MA), intermediate/degraded quality (6-CA, 5- MA and 7-SU), degraded quality (1-CG, 2-MA and 4-MA). In the 2nd collection: high quality (5-MA, 6-CA and 7-SU), intermediate/high quality (2-MA, 3-MA and 8-GC), intermediate/degraded quality (4-MA), degraded quality (1-GC). The results of this study suggest that the quality of the sediment infralitoral (1-CG, 2-MA e 4-MA) have more evidence of degradation induced by contamination of the stations of mesolitoral.